2014
DOI: 10.1097/01.epx.0000445305.88786.9e
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the safety of injection practices and injection-related procedures in family health units and centers in Alexandria

Abstract: Indicators related to injection and injection-related practices that reflect risk to patients include deficiency of alcohol-based hand rub tools, nonadherence to hand hygiene before preparing an injection, and inadequate adherence to using a clean barrier when opening a glass ampule and use of gloves. Indicators that may reflect risk to patients and providers include inadequate injection safety training and incomplete hepatitis B vaccination of healthcare providers. Indicators that may reflect risk to provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
2
5
0
3
Order By: Relevance
“…In our study, 15% of participants stated that they had at least one exposure to NSIs in the previous 6 months. This percentage is similar to that reported in Jazan [ 12 ] and Alexandria [ 13 ], but lower than those reported by other studies [ 1 , 9 , 14 ]. This could be attributed to the higher risks of exposure in hospitals due to higher rate of injections administered.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, 15% of participants stated that they had at least one exposure to NSIs in the previous 6 months. This percentage is similar to that reported in Jazan [ 12 ] and Alexandria [ 13 ], but lower than those reported by other studies [ 1 , 9 , 14 ]. This could be attributed to the higher risks of exposure in hospitals due to higher rate of injections administered.…”
Section: Discussionsupporting
confidence: 89%
“…The percentage of injection providers who received full doses of hepatitis B vaccinations was similar to the one reported in a Saudi study in Jazan Region [ 13 ] and even higher than those reported by similar studies in different Egyptian regions [ 11 , 12 , 14 ] and in an Indian study [ 23 ]. However, full immunization of all health workers is needed and should be considered a fundamental right as Egypt has the highest rate globally for hepatitis B and C for the last 20 decades [ 22 ] with their life-long and life-threatening complications.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Respecto a las prácticas documentadas en la literatura, el personal utiliza insumos provenientes de paquetes estériles, cerrados y desechables, y su preparación se lleva a cabo en espacios limpios. Son las acciones subsecuentes como el reúso de los dispositivos, la contaminación de los viales y soluciones y los lapsus en la técnica aséptica, los que afectan la seguridad del procedimiento y contradicen los estudios que arman que el personal posee los conocimiento adecuados (32,34,35,(38)(39)(40)42,45,(48)(49)(50).…”
Section: Discussionunclassified